2017
DOI: 10.1002/uog.17399
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy of competing‐risks model in screening for pre‐eclampsia by maternal factors and biomarkers at 11–13 weeks' gestation

Abstract: Assessment of a combination of maternal factors and biomarkers at 11-13 weeks provides effective first-trimester screening for preterm PE. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
228
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(243 citation statements)
references
References 18 publications
11
228
0
4
Order By: Relevance
“…With use of Bayes’ theorem to combine the a priori risk from maternal factors with uterine artery pulsatility index (UtA‐PI), mean arterial pressure (MAP), and serum placental growth factor (PlGF) at 11–13 weeks’ gestation, a study involving about 60 000 singleton pregnancies reported that such screening detected 76% and 40% of pregnancies at high‐risk of preterm and term pre‐eclampsia, respectively, at a false‐positive rate of 10% . A prospective external validation study of 8775 singleton pregnancies, including 239 (2.7%) cases that developed pre‐eclampsia, has further confirmed that the first trimester combined test achieves detection rates of 75% and 43%, respectively, for preterm and term pre‐eclampsia, at a 10% false‐positive rate …”
Section: Screeningmentioning
confidence: 99%
“…With use of Bayes’ theorem to combine the a priori risk from maternal factors with uterine artery pulsatility index (UtA‐PI), mean arterial pressure (MAP), and serum placental growth factor (PlGF) at 11–13 weeks’ gestation, a study involving about 60 000 singleton pregnancies reported that such screening detected 76% and 40% of pregnancies at high‐risk of preterm and term pre‐eclampsia, respectively, at a false‐positive rate of 10% . A prospective external validation study of 8775 singleton pregnancies, including 239 (2.7%) cases that developed pre‐eclampsia, has further confirmed that the first trimester combined test achieves detection rates of 75% and 43%, respectively, for preterm and term pre‐eclampsia, at a 10% false‐positive rate …”
Section: Screeningmentioning
confidence: 99%
“…Previous PE of the pregnant woman and/or of her mother and sisters has already been identified as a major risk factor, along with black ethnicity [87], [88]. We use the term black ethnicity as statistics have shown higher rates of PE in Africa compared to Europe, and among Afro-Americans and Afro-Caribbeans compared to Caucasians.…”
Section: Targeted Approach To Combat Preeclampsiamentioning
confidence: 99%
“…EOPE, early-onset preeclampsia; E2, estradiol; LOPE, late-onset preeclampsia; MBL, mannose binding lectin; P4, progesterone; SP-A, surfactant protein A; SP-D, surfactant protein D. P < .05 represents a significant correlation using the Spearman method factors [eg, mean arterial pressure (MAP) and uterineartery Doppler Pulsatility Index (PI)] are being used to develop an appropriate prediction model for PE 45. Owing to severity of EOPE and associated maternal and fetal mortality and morbidity, an early detection (<14th week of gestation) has been recommended for the initiationF I G U R E 7 Correlation of P4/E2 ratio with collectins.…”
mentioning
confidence: 99%